Voluntariness or legal obligation? An ethical analysis of two instruments for fairer global access to COVID-19 vaccines - Voit, Katja; Timmermann, Cristian; Orzechowski, Marcin; Steger, Florian (Frontiers in Public Health, 2023)
There is currently no binding, internationally accepted and successful approach to ensure global equitable access to healthcare during a pandemic. The aim of this ethical analysis is to bring into the discussion a legally regulated vaccine allocation as a possible strategy for equitable global access to vaccines. We focus our analysis on COVAX (COVID-19 Vaccines Global Access) and an existing EU regulation that, after adjustment, could promote global vaccine allocation. The main documents discussing the two strategies are examined with a qualitative content analysis. The ethical values reasonableness, openness and transparency, inclusiveness, responsiveness and accountability serve as categories for our ethical analysis. We observed that the decision-making processes in a legal solution to expand access to vaccines would be more transparent than in COVAX initiative, would be more inclusive, especially of nation states, and the values responsiveness and accountability could be easily incorporated in the development of a new regulation. A legal strategy that offers incentives to the pharmaceutical industry in return for global distribution of vaccines according to the Fair Priority Model is an innovative way to achieve global and equitable access to vaccines. However, in the long term, achieving the Sustainable Development Goals will require from all nations to work in solidarity to find durable solutions for global vaccine research and development. Interim solutions, such as our proposed legal strategy for equitable access to vaccines, and efforts to find long-term solutions must be advanced in parallel.